Building skills, knowledge and confidence in eating and exercise behavior change: Brief motivational interviewing training for healthcare providers. Issue 5 (May 2015) - Edwards, Elizabeth J.; Stapleton, Peta; Williams, Kelly; Ball, Lauren
Highlights Healthcare providers were trained in brief motivational interviewing. Training showed increases in brief motivational interviewing knowledge, skills and confidence. A short workshop can train healthcare workers in eating and exercise behavior change.